Computational modelling in science, technology, engineering and mathematics education - Neves, Rui (2017)
Modelling is a central aspect of the research process in science, technology, engineering and mathematics (STEM) which occurs in the cognitive contexto of an interactive balance between theory, experiment and computation. The STEM learning processes should then also involve modelling in environments where there is a balanced interplay between theory, experiment and computation. However, an adequate integration of computational themes in STEM high school and undergraduate university curricula remains to be achieved. In this work, we present an approach to embed computational modelling activities in the STEM learning process which may be fruitfully adopted by high school and university curricula, as well as be a valuable instrument for the professional development of teachers. To illustrate, we consider the example of physics.